Prevalence, pattern and risk factors for domestic violence against men in Sokoto Metropolis of Sokoto state, Nigeria - M. Oche, Oche; Adamu, Habibullah; Raji, Ismail; Musa, Yahaya; Danmadami, Abdulaziz; Ezenwoko, Ahunna Z.; A. Kontagora, Zainab (International Journal Of Community Medicine And Public Health, 2024)
Background: Domestic violence against men (DVAM) is a major public health concern all over the world and remains unheard of because of the shame, guilt and embarrassment associated with it. This study was aimed at determining the prevalence, pattern, knowledge and risk factors for DVAM in Sokoto metropolis. Methods: A descriptive cross-sectional study was carried to assess the prevalence, patterns and risk factors for domestic violence against men in Sokoto metropolis. Using a multistage sampling method, a total of 141 men were recruited into the study and administered with a standardized questionnaire. Data was entered and analyzed using IBM statistical package for the social sciences (SPSS) statistical software version 25 and thereafter summarized using frequencies and percentages. Bivariate and multivariate analyses were carried out to determine level of associations and predictors of DVAM. Results: Almost half (49%) of the respondents were aware of DVAM while most (73.3%) had good knowledge of violence against men. The forms of violence experienced by the respondents include psychological (90.8%), physical (20%), and Sexual (90.8%). All the respondents experienced at least one form of violence and risk factors for violence included use of alcohol and other illicit drugs and keeping late at night. Conclusions: Men are increasingly becoming victims of domestic violence with little or no attention being given to their plight as they are seen more as the aggressors. There is a need to take a holistic approach to the issues of domestic violence generally and the domestication of laws against violence perpetrated against men.